An integrative model for understanding team organizational citizenship behavior: Its antecedents and consequences for educational teams. Issue 6 (4th September 2017) - Somech, Anit; Khotaba, Soha
Abstract : Purpose: The purpose of this paper is to use a model to broaden the understanding of the organizational citizenship behavior (OCB) phenomenon in educational teams and examines team OCB's mediating role in the relation of the contextual variables of team justice climate (distributive justice, procedural justice, interpersonal justice) to team psychological capital (PsyCap) and team innovation. Design/methodology/approach: Data were collected through a survey consisting of validated scales. The sample covered 78 disciplinary teams, 78 coordinators and 13 school principals at 13 junior-high schools. Findings: The PROCESS test confirmed the mediating role of team OCB, showing positive relations between team procedural justice and team PsyCap and team OCB, and also between team OCB and team innovation. Research limitations/implications: By taking a team perspective, the findings offer evidence that despite the usual approach treating OCB as an individual phenomenon; it may be regarded as shared norms of behaviors at the team level. Practical implications: The team-level approach may urge principals and other educational leaders to realize that teachers' willingness to invest extra effort in school is mainly the result of an appropriate team context, which can be shaped and developed. Originality/value: The present study explored team OCB by from a context perspective. This is important because to date most studies on OCB in schools have focused on teacher OCB as an individual phenomenon, disregarding its contextual nature.